El uso de infraestructura de electricidad por empresas de telecomunicaciones - Soto Carrillo, Gerardo (2023)
The need to deploy telecommunication networks in Peru has generated the approval of various legal regimes that oblige electricity utilities (transmission and distribution) to allow the use of their facilities by telecommunication companies, mainly to install optical fiber. These regimes have given rise to various criteria derived from the multiplicity of administrative disputes that have been decided by the regulator. As a result, specific procedures have been issued, including mandatory orders (mandates) from the telecommunications regulator to the electricity companies, in some cases with price regulation.Along these lines, this article describes and analyses these regimes, as well as the regulator’s criteria, with certain points remaining in dispute.